2011
DOI: 10.1590/s0100-29452011005000041
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry pollination in southern Brazil and their influence on fruit quality

Abstract: -Blueberry (Vaccinium ashei) is a relatively new crop in cultivation under Southern Brazil conditions. The first collection introduced in the area was formed by rabbiteye cultivars which need insect pollinators and also pollinizers. The aim of this work was to observe if there were differences between pollinizers on fruit quality of the commercial cultivar and also to observe the most effective and frequent insect pollinators, under natural conditions. It was concluded that pollen source has an effect on quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…This phenomenon is known as metaxenia, where the pollen donor genotype may influence the physical and biochemical quality of the guava fruits (Usman et al, 2013). It has also been reported in apple (Bodor et al, 2008), blueberry (Silveira et al, 2011) and loquat crops (Xu et al, 2007). This observation suggests that it is possible to select pollinating genotypes in order to constitute a commercial orchard with the aim of increasing productivity and fruit quality.…”
Section: Introductionmentioning
confidence: 64%
“…This phenomenon is known as metaxenia, where the pollen donor genotype may influence the physical and biochemical quality of the guava fruits (Usman et al, 2013). It has also been reported in apple (Bodor et al, 2008), blueberry (Silveira et al, 2011) and loquat crops (Xu et al, 2007). This observation suggests that it is possible to select pollinating genotypes in order to constitute a commercial orchard with the aim of increasing productivity and fruit quality.…”
Section: Introductionmentioning
confidence: 64%
“…Parasitoids of families Ichneumonidae and Braconidae were also collected, however, their hosts were not identified. According to Silveira et al (2011), bumblebees of the genus Bombus are the most efficient pollinators of blueberry under southern Brazil conditions while bees play a complementary role.…”
Section: Resultsmentioning
confidence: 99%
“…(RECALDE, 2008), while in the region on the west bank of the Uruguay River, the fruit flies Anastrepha fraterculus (Wiedemann) and Ceratitis capitata (Wiedemann) were recorded (GORDÓ, 2008). In Brazil, the existing information on insect pests associated with blueberry is scarce with studies on Naupactus tremolesari L., Tolype innocens (Burmeister), Trigona spinnipes (Fabricius) and Eurhizococcus brasiliensis (Wille) (GONÇALVES et al, 2009;LOUZADA et al, 2011;SILVEIRA et al, 2011;EFROM et al, 2012). Thus, the objective of this study was to know the insect fauna associated with the different phenological stages of the blueberry crop in Pelotas area, Rio Grande do Sul State, in order to obtain support for implementing integrated pest management to this culture.…”
Section: Introductionmentioning
confidence: 99%
“…They are able to grow and flourish with only 360 hours of chilling, while those in the group "highbush" need between 650 and 800 hours of chilling [10]. Silveira et al [19] found that even the source of pollen is important for the quality of fruits of the variety "rabbiteye" produced in the Southern region of Brazil. In addition, Rocha [11] remarks that the variety Bluegem, from the group "rabbiteye", is one of the most widely grown in the Southeastern region of Brazil due to its wide adaptation and lower cold requirement.…”
Section: Fruit Traits and Productionmentioning
confidence: 99%